Effective Teaching Methods for Speaking Skill for Undergraduates - Ive Emaliana (Jurnal VOK@SINDO, 2014)
This study is aimed at investigating students’ learning needs which are taken from students’ questionnnaire about self-evaluation and course evaluation particularly about speaking skill in English specific purposes course. The questionnaire includes four variables, namely learning motivation, attitude towards teaching method, attitude towards teaching materials, and problems faced by students. 449 non-English department students become the respondents, and the questionnaire results yield students learning needs and evaluation. Some teaching methods are used in the teaching of speaking, namely poster display, presenting advertisement, and cellphone video recording. By knowing the students’ learning needs and learning evaluation, teachers can decide effective teaching methods that can raise students’ motivation in learning English